Identification of thermal properties of solids by means of solving the inverse problem using evolutionary algorithms and optimal dynamic filtration - Kucypera, Stanisław (Computer Assisted Methods in Engineering and Science, 2022)
The aim of the paper is to combine the evolutionary algorithms method, optimal dynamic filtration method and measurement data for the simultaneous identification of the thermal properties or their temperature characteristics of anisotropic solids. The idea of the proposed method depends on measuring the timedependent temperature distribution at selected points of the sample and identification of the thermal parameters (heat conductivity and specific heat) by solving a transient inverse heat conduction problem. In the paper the discrete mathematical model has been formulated basing on the control volume method. The inverse problem as solved by using a hybrid method. Information about measurement data which are necessary to solve the inverse heat conduction problem was obtained by solving the direct heat conduction problem. The chosen results of analysis have been presented.